Chemical changes of thermally sterilized broccoli puree during shelf-life: Investigation of the volatile fraction by fingerprinting-kinetics. (January 2015) - Kebede, Biniam T.; Grauwet, Tara; Magpusao, Johannes; Palmers, Stijn; Michiels, Chris; Hendrickx, Marc; Van Loey, Ann
Abstract: For the first time in literature, this study evaluates the potential of a "fingerprinting-kinetics" strategy to investigate how the volatile fraction of thermally sterilized broccoli puree is affected by shelf-life. Samples were stored at four storage temperatures (20 °C, 28 °C, 35 °C and 42 °C). The volatile fraction was analyzed using headspace GC-MS fingerprinting as a function of time and temperature (kinetics). Fingerprinting enabled selection of sulfur-containing compounds (dimethyl sulfide, carbon disulfide, dimethyl pentasulfide, dimethyl trisulfide, bis-(methylthio)-phosphine and methyl (methylthio)methyl disulfide), nitriles (heptanonitrile, 5-methyl-hexanenitrile, hexanenitrile and 5-(methylthio)-pentanenitrile), fatty acid derivatives (octanal and 2-ethyl-1-hexanol), furanic compounds (2-ethylfuran) and Strecker aldehydes (3-methylbutanal) as volatiles significantly changing during shelf-life. In general, most of the volatiles decreased as a function of shelf-life. Next, the suitability of the volatiles (selected by fingerprinting) as markers for accelerated shelf-life testing was investigated. Based on the applied kinetic modelling, 3-methylbutanal was identified as a potential marker. Highlights: A fingerprinting-kinetics strategy enabled a better insight into shelf-life changes. The volatile fraction of sterilized broccoli puree changes during shelf-life. Most of the volatile compounds decreased during storage. 3-Methylbutanal was selected as a marker for accelerated shelf-life testing.